Technologies of Responsibility Development in Vocational Training - Sherban T. D., Ноblyk V. V., Prib H.A., Bretsko I. І., Beheza L. Е., Reznik N. P (International Journal of Advanced Science and Technology, 2020)
Successful fulfillment of professional tasks depends not only on the knowledge and skills of the individual, but also on the individual-psychological qualities of the character that determine professional identification. Responsibility is a marker of professional identification. Therefore, an important task of higher education is the development of responsible attitude to work, which is the basis of students’ psychological readiness for the future profession. The psychological features of technologies for developing responsibility for future professional activities during studies at a higher educational institution are insufficiently studied. The aim of the research is to study the psychological features of the responsibility development for future professional activity.